2014
DOI: 10.1590/s1983-41952014000400008
|View full text |Cite
|
Sign up to set email alerts
|

O papel do metacaulim na proteção dos concretos contra a ação deletéria de cloretos

Abstract: O objetivo deste trabalho é avaliar a capacidade de proteção de concretos produzidos com metacaulim em relação ao transporte e penetração de cloretos. Para tanto, a partir de um concreto comercial de fck igual a 30 MPa, foram produzidos mais dois concretos substituindo-se 10% da massa de cimento por metacaulim, a saber: em um dos concretos manteve-se a mesma relação água/aglomerante do traço inicial de referência (a/ag = 0,60) e no outro manteve-se fixa a resistência à compressão. Em todas as três dosagens foi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
2
11
0
1
Order By: Relevance
“…Due to the environmental impact caused by the extraction of raw materials and CO 2 emission in cement production has been sought a reduction of the consumption of this constituent of concrete, together with the need to increase the durability [3], [4]. In this context, it arises as an alternative the using supplementary cementitious materials (SCMs) in partial replacement to Portland cement [4]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the environmental impact caused by the extraction of raw materials and CO 2 emission in cement production has been sought a reduction of the consumption of this constituent of concrete, together with the need to increase the durability [3], [4]. In this context, it arises as an alternative the using supplementary cementitious materials (SCMs) in partial replacement to Portland cement [4]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of other ions in the pore solution (ions of Na + , K + , Ca 2+ , OH À , etc.) influences the rate of entry of Cl À , accelerating or slowing its penetration (via mechanisms of repulsion or attraction among electrical charges) [25]. Also, the filling of micropores with SBAS particles, especially pores with dimensions smaller than 150 lm, may modify the mortar microstructure, resulting in a less permeable mortar.…”
Section: Analysis Of Chloride Penetration In Mortarsmentioning
confidence: 99%
“…Dinakar et al 24 evaluated the mechanical and durability properties of concrete containing 5%, 10% and 15% of ME substitution, and concluded that 10% was the optimal level in terms of compressive strength, and that durability gains are directly proportional to the increase of the replacement percentage. Figueiredo et al 25 evaluated the chloride-contaminated layer in saline solution using a colorimetric indicator, and found that, concrete with 10% ME as cement replacement and w/c ratio of 0.60, showed a reduction of chloride penetration of $20%.…”
Section: Introductionmentioning
confidence: 99%
“…Figueiredo et al. 25 evaluated the chloride-contaminated layer in saline solution using a colorimetric indicator, and found that, concrete with 10% ME as cement replacement and w / c ratio of 0.60, showed a reduction of chloride penetration of ∼20%.…”
Section: Introductionmentioning
confidence: 99%